Effect of Oxygen Impurity on Thermal Conduction Rate of Polycrystalline Si3N4. Issue 10 (29th July 2021) - Dow, Hwan Soo; Na, Moonkyong; Jung, Yeon Wook; Geun Jo, Seung; Lee, Jung Woo
Abstract : Herein, the thermophysical properties and microstructures of the densified Si3 N4, which are prepared by using MgO, Y2 O3, and oxygen getter as sintering additives via conventional hot‐pressing sintering and followed by postheat treatment, are reported. Herein, it is found out that the sample using 5 mol.% of MgO, 2 mol.% of Y2 O3, and 1.5 mol.% of Nb has the optimized thermal conductivity of 108 W m −1 ·K. Furthermore, increased rate of thermal conduction in the range of 10–15% is mainly originated from the decrease in the lattice oxygen contents of the grains in Si3 N4 based on electron spin resonance (ESR) analysis. Abstract : Herein, the heat transfer of binary Si3 N4 system with homogeneous structures and the oxygen getter effects is reported. The oxygen defects in Si3 N4 grains are phonon scattering centers that induce spontaneous diminution of the transfer of thermal energy.